Pengaruh Terapi Relaksasi Otot Progresif Terhadap Penurunan Tekanan Darah Pada Wanita Lanjut Usia Dengan Hipertensi Primer Di Posyandu Lansia Peduli Insani Mendungan Surakarta - Afriani Khasanah, Dini; , Yulisna Mutia Sari, SSt.FT., M.Sc (GRS) (2017)
ABSTRACT Background : The elderly especially women began to decline in the body function one of the ciculatory system. A decrease in elasticity of artery walls that can lead to increased blood pressure in the elderly. One way in which to do is progressive muscle relaxation therapy. Progressive muscle relaxation therapy in elderly aims to envoke the relaxation response that can stimulate the sympathetic dan parasympathetic nervous activity resulting in descreased blood pressure in elderly. Research Aims : To determine the effect of progressive muscle relaxation therapy to decrease blood pressure the elderly women with primary hypertension. Methods : Kind of research is Quasi Experimental Design with research design is Pretest-Posttest With Control Group Design. The sampling technique used is Purposive Sampling Technique. The total sample is 17 peoples. Results : The result of Mann Whitney test systolic pressure values obtained in the control group and the treatment group is p value (0,031) and diastolic pressure in the control group and the treatment group is p value (0,261). Conclusion : Progressive muscle relaxation therapy effect to the decrease in systolic blood pressure but did not affect the reduction in diastolic blood pressure the elderly women with primary hypertension at elderly Posyandu Peduli Insani Mendungan Surakarta. Keywords : Progressive Muscle Relaxation Therapy, Blood Pressure, Women, Elderly, Primary Hypertension.